Controlled growth of silicon nanocrystallites in silicon oxide matrix using 150 MeV Ag ion irradiation - Chaudhari, P. S.; Bhave, T. M.; Pasricha, R.; Singh, F.; Kanjilal, D.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2005)
We report the synthesis of silicon nanocrystals grown in silicon oxide matrix by swift heavy ion irradiation. Thin films of silicon oxide (SiO(x)) are irradiated with 150 MeV silver ions at fluence varying from 5 x 10(11) to 1 x 10(13) ions/cm(2). The variation in the properties of silicon nanocrystals embedded in silicon oxide with varying fluence is studied. The energy of the photoluminescence peak corresponding to the silicon nanocrystals is found to be red shifted with increasing fluence. The trends in the broadening of the X-ray diffraction peak with decreasing fluence supports the controlled growth of silicon nanocrystals in silicon oxide matrix. The crystallite size of nanoclusters of silicon is seen to increase with increasing fluence. The results are discussed in view of the structural transformation, in SiO(x) matrix, caused by swift heavy ion irradiation. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oxide matrix; silicon nanocrystallites; swift heavy ion irradiation

Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Co-precipitation technique for the preparation of ferroelectric BaBi2Ta2O9 - Dhage, S. R.; Pasricha, R.; Murugan, A. Vadivel; Ravi, V. (Materials Chemistry and Physics, 2006)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase BaBi2Ta2O9 (BBT). Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Ta5+ cations simultaneously. No pyrochlore phase was found while heating powder at 800 degrees C and pure BaBi2Ta2O9 phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 350. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides